2016
DOI: 10.1039/c6nj01831a
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties of Eu2+-doped BaSi2O5 as an efficient green phosphor for light-emitting devices and wide color gamut field emission displays

Abstract: A green-emitting BaSi2O5:Eu2+ phosphor for white light emitting diodes and field emission displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…There are many factors in choosing an ideal and useful dosimetric material for luminescence studies. As one of the most significant compounds, silicates are extensively used as the matrix of inorganic phosphors due to their advantages such as easy synthesis, good thermal quenching, high chemical stability, and ideal excitation and emission wavelengths [1,2]. Especially, alkaline-earth silicates are appropriate compounds as radiation detectors due to their water resistance and chemical stability, and exceptional storage luminescence properties have been explicated for dosimetry [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors in choosing an ideal and useful dosimetric material for luminescence studies. As one of the most significant compounds, silicates are extensively used as the matrix of inorganic phosphors due to their advantages such as easy synthesis, good thermal quenching, high chemical stability, and ideal excitation and emission wavelengths [1,2]. Especially, alkaline-earth silicates are appropriate compounds as radiation detectors due to their water resistance and chemical stability, and exceptional storage luminescence properties have been explicated for dosimetry [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The barium silicate compound comprises different compositions as a host material with the various ratios of BaO and SiO 2 , namely Ba 2 SiO 4 , BaSiO 3 , Ba 2 Si 3 O 8 , Ba 5 Si 8 O 21 , and BaSi 2 O 5 [7]. Among them, BaSi 2 O 5 has attracted much attention by aiming a potential in luminescence investigations especially, Eu-doped BaSi 2 O 5 phosphors [2,6,[8][9][10] are stated to be a potential candidate for white light-emitting diodes, field emission displays, and TL dosimetry. Doping may either cause the formation of new defect centers or recovering of existing levels within the bandgap for a defective host which changes both the optical and electronic features of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Gilliland et al. proposed the phosphor BaSi 2 O 5 :Pb 2+ , demonstrating that BaSi 2 O 5 is a promising host for investigating the long persistent phosphorescence materials; Nakanishi et al and Cao et al also reported the luminescent properties of Eu 2+ ion-doped BaSi 2 O 5 phosphors, proving that BaSi 2 O 5 :Eu 2+ is an efficient phosphor for light-emitting devices. However, to the best of our knowledge, there is no report about the LLP properties of BaSi 2 O 5 :Eu 2+ , Ln 3+ (Ln = Dy, Pr, Ce, Nd, Tb, Ho, Tm, Er).…”
Section: Introductionmentioning
confidence: 99%
“…However, being FEDs composed by an array of aligned field emitter tips cathodes opposite to a phosphor anode, their development has been limited by the complexity of the device fabrication and by the presence of contaminants released under the high-electron bombardment and related to the used phosphor. Therefore a big part of the scientific community working on FEDs is nowadays focused on the development of novel stable materials emitting in the visible range with high luminance, good chromaticity, long service time, high efficiency at low voltages (<5 keV) 2,3 . Similarly, for white or tunable LEDs application, many efforts are devoted to developing down-conversion luminescent materials for phosphor-converted LEDs (pc-LEDs) that are competitive in view of the low cost and the simplicity of the control circuit 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…About the hosts, the most commercially available for FEDs are the sulfide-based ones, such as CaSO 4 :Tb, Na 10 , but unfortunately they suffer from some limits, such as the quick degradation due to the corrosive sulfide gases produced under high-electron bombardment 2 . To overcome these drawbacks, many alternative RE-doped nanomaterials 11,12 , and phosphors 3,13 , have been proposed, among whom several RE doped oxides, such as Y 2 SiO 5 :Ce 3+  14 , LiAl 5 O 8 :Tb 15 and ZnGaO 2 16 and nitrides, such as Eu:AlN 17 , have been studied as possible solution.…”
Section: Introductionmentioning
confidence: 99%